LEARNING ASSESSMENT IN THE MERDEKA CURRICULUM: DIAGNOSTIC, FORMATIVE, AND SUMMATIVE - Siti Khodijah Lubis; Siti Syawalina (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2024)
This research aims to outline the assessment process in the Merdeka curriculum, encompassing diagnostic, formative, and summative assessments. The approach utilized involves conducting a review of the literature, by gathering information through exploration of different written sources. Content analysis is utilized in data analysis. The study findings reveal that the diagnostic assessment consists of cognitive and non-cognitive assessments designed to evaluate students' condition and fundamental skills. Formative assessment occurs during the learning process, while summative assessment occurs after a specific instructional period. Teachers must conduct diagnostic, formative, and summative assessments to understand the strengths and weaknesses of student learning during the learning process to tailor instruction to fit the abilities and characteristics of each student.